1998
DOI: 10.1002/jlb.64.6.800
|View full text |Cite
|
Sign up to set email alerts
|

CD43 is associated with tyrosine kinase activity in human neutrophils

Abstract: CD43 appears to be involved in signal transduction, however, the mechanism of this function is unknown. Protein kinase activity was detected in neutrophils associated with CD43. Most of the protein kinase activity associated with these antigens was tyrosine kinase activity. The src family kinases lyn and hck were found to account for much of the associated tyrosine kinase activity. The data suggest that associated tyrosine kinase activity may play a role in signal transduction via CD43 to regulate other cell f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 19 publications
2
85
0
2
Order By: Relevance
“…Furthermore, we have shown that inhibition of CEA-CAM6 expression reduces Akt phosphorylation at Ser-473, an indicator of Akt activity directly influenced by c-Src activity (Downward, 1998). CEACAM family molecules have been reported to associate with Src family kinases (Skubitz et al, 1995). Although this study was not designed to address the molecular interaction between CEACAM6 and c-Src, we observed that CEACAM6 overexpression increased c-Src kinase activity.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, we have shown that inhibition of CEA-CAM6 expression reduces Akt phosphorylation at Ser-473, an indicator of Akt activity directly influenced by c-Src activity (Downward, 1998). CEACAM family molecules have been reported to associate with Src family kinases (Skubitz et al, 1995). Although this study was not designed to address the molecular interaction between CEACAM6 and c-Src, we observed that CEACAM6 overexpression increased c-Src kinase activity.…”
Section: Discussionmentioning
confidence: 76%
“…Given that CEACAM family members are known to associate with Src family kinases (Skubitz et al, 1995), we hypothesized that c-Src may play a role in activating Akt. c-Src kinase activity was measured by in vitro kinase assay and, consistent with our hypothesis, both pIRES-CEACAM6 transfectants demonstrated significantly elevated c-Src kinase activity, compared to both pIRES-eGFP transfectants and Capan2 cells, which showed no difference in their relative c-Src kinase activities ( Figure 4a).…”
Section: Ceacam6 Overexpression Increases Akt Kinase Activitymentioning
confidence: 99%
“…However, C-CAM1 expression was accompanied by changes in the expression of other non-CAM related, MAb-de®ned epitopes, changes which may relate directly or indirectly to the adhesive or other signal transducing activities of C-CAM1 Brummer et al, 1995;Najjar et al, 1995;Sippel et al, 1994;Skubitz et al, 1995). This possibility was exempli®ed by the C-CAM1 associated decrease in OV6, an epitope shared by CK14 and CK19, members of a large family of cytoskeletal intermediate ®lament proteins that play important roles in the maintenance of intracellular organization as well as cell integrity and shape (Goldman et al, 1990;Green and Jones, 1990;Lazarides, 1980;Marceau and Loranger, 1995;Omary and Ku, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The adhesive activity of C-CAM1 is well established with the ®rst immunoglobulin domain being essential for adhesion (Cheung et al, 1993a). More recent evidence showing that the cytoplasmic domain of C-CAM1 is tyrosine phosphorylated by pp60 c-src in epithelial cells (Brummer et al, 1995) and p53-56 lyn in neutrophils (Skubitz et al, 1995), is serine phosphorylated on Ser-503 (Najjar et al, 1995;Sippel et al, 1994) and binds the SHP-1 tyrosine phosphatase . This suggests that C-CAM1 may also play a role in signal transduction, the biological outcomes of which remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…2 In agreement with our results, Lozano et al (32) have reported inducible serine phosphorylation of ICAM-3. In contrast, Skubitz et al (34) reported inducible phosphorylation predominantly on tyrosine. This discrepancy may be attributed to differences in cell isolation procedures or the manner in which the cells were labeled.…”
Section: Expression Of Icam-3 In J77503 Cells Restoresmentioning
confidence: 90%